Document Analysis of the Impact of Empowerment Modules in Internship Programs at PKBM Alam Jingga, Indonesia - Robianti, Febi; Raufu, Mufutau; Sasongko, Marsahid; Raufu, Sikirat; Raufu, Jemilat; Yamani, Khalila (Jurnal Pendidikan Non formal, 2024)
This study examines the integration of empowerment modules into internship programs at PKBM Alam Jingga, an Indonesian institution dedicated to holistic education through nature-based learning. The modules aim to enhance students' personal development by cultivating critical thinking, creativity, and global citizenship skills. Additionally, the research focuses on how these modules align with the Pancasila student profile, promoting values such as faith, noble character, and community spirit—essential for nurturing responsible and culturally aware individuals. Utilizing a document analysis method, feedback from students, instructors, and supervisors was evaluated through models like Kirkpatrick's and CIPP to assess the program's effectiveness. The findings demonstrate that the empowerment modules significantly contribute to students' academic and personal growth, fostering deeper engagement with their education and societal roles. This study underscores the importance of refining internship practices to address the evolving demands of the workforce while maintaining alignment with the core values of Pancasila. The integrated approach offers a framework for developing well-rounded individuals, equipped for both career success and meaningful contributions to society.